Impact of health literacy and illness perception on medication adherence among older adults with hypertension in Iran: a cross-sectional study - Babazadeh, Towhid; Ranjbaran, Soheila; Pourrazavi, Sara; Latifi, Arman; Maleki Chollou, Khalil (Frontiers in Public Health, 2024)
Background: Adherence to medication is an essential factor in controlling and reducing the side effects of non-communicable diseases, particularly hypertension. Medication adherence varies in older adults due to the effects of various factors. The research aimed to examine the determinants of medication adherence among older adults with hypertension.Methods: This cross-sectional study was performed among 300 people aged 60 years or older referring to health centers in Sarab, Iran, between February and May 2023. To collect data, valid and reliable tools were applied.Results: There was a significant association between age groups, level of education, and monthly income status with adherence to medication (p-value < 0.05). According to the results of hierarchical regression, demographic variables collectively explained 3.2% of the variance in adherence to therapeutic regimens (p-value = 0.143). The inclusion of illness perception at step 2, along with demographic variables, led to a further significant increase in 9.6% of the variance (p-value < 0.001). In the final step, health literacy dimensions were added, which explained an additional 8.7% of the variance (p-value < 0.001). In total, demographic variables, illness perception, and HL dimensions explained 21.5% of the variance in adherence to therapeutic regimens.According to the results, demographic variables, illness perception, and HL dimensions were the main determinants of medication adherence among older adults. Health educators should focus on creating interventions that improve medication adherence by addressing illness perception and health literacy dimensions in this particular population.